Design and development of management system for reserve talents of competitive sports - Shi, Q.; Yang, T. (Proceedings of the Second International Conference on Computer Modeling and Simulation, 2010, 2010)
Based upon the analysis of management system for reserve talents of competitive sports and in accordance with the software engineering requirements, the management system for reserve talents of competitive sports is designed and developed. The system integrates the basic information, evaluation, statistics and decision-making models, and various kinds of athletic competency models of elite athletes, realizes the scientization, automation and man-machine integration in the reserve talents management, and thus provide a powerful decision support for the scientific management and implementation of reserve talents for competitive sports.